2015
DOI: 10.1002/mame.201500156
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Degradation of LDPE by Compact NMR

Abstract: Morphological and structural changes of commercial-brand low-density polyethylene induced by thermal aging for different times at different temperatures are studied by compact 1 H NMR relaxation, FTIR spectroscopy, and SEC including the impact of wax content. Two regimes were observed. The changes in phase composition and relaxation time suggest that thermally induced crystallization is predominant during aging and oxidation of LDPE below 100 8C while, after 28 d aging at 100 8C, oxidative degradation is predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
5
25
0
1
Order By: Relevance
“…This is accompanied by a reduction in the fraction of the interface domains and an increase in the fraction of the amorphous domains. The latter result agrees well with the variations in the chain mobility of the soft domains (Figure a) and the phase composition determined by compact NMR . Compared to thermal aging, the phase composition of LDPE shows a slighter variation upon swelling in n‐hexane where the rigid fraction determined by compact NMR at room temperature increases by almost one percent by weight .…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…This is accompanied by a reduction in the fraction of the interface domains and an increase in the fraction of the amorphous domains. The latter result agrees well with the variations in the chain mobility of the soft domains (Figure a) and the phase composition determined by compact NMR . Compared to thermal aging, the phase composition of LDPE shows a slighter variation upon swelling in n‐hexane where the rigid fraction determined by compact NMR at room temperature increases by almost one percent by weight .…”
Section: Resultssupporting
confidence: 86%
“…To understand the structural changes induced by thermal aging and observed by NMR, FTIR spectra were measured and the carbonyl index I CO determined for different aging times and temperatures (Figure a). For the LDPE samples aged at 80 and 90° C, a gradual increase in I CO is observed, indicating the occurrence of chain scission even at short exposure times . These results were corroborated by SEC measurements which revealed that the molecular weight decreases in the whole range of exposure times and at all three temperatures.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations